Utilization of MEA medium for isolation and characterization of white oyster mushroom (Pleurotus ostreatus) and growth assessment on baglog - Purwitasari, Nuril Azmi; Umayah, Abu; Pratama, Rahmat; Safitri, Ayu (Journal of Scientific Agriculture, 2025)
White oyster mushrooms (Pleurotus ostreatus) are widely cultivated in Indonesia. Oyster mushroom cultivation is one of the export commodities that help to meet food needs. Pleurotus sp. requires an appropriate environment for developing these mushrooms, utilizing suitable planting media. Oyster mushroom media can be straw media or sawdust media. South Sumatra oyster mushroom cultivation uses sawdust media for 57.90% of white oyster mushroom cultivation, and straw media as an alternative for 100% white oyster mushroom cultivation. This research was conducted at the Phytopathology Laboratory, Department of Plant Pests and Diseases, Plant Protection Study Program, Faculty of Agriculture, Sriwijaya University, Indralaya, South Sumatra. Oyster mushroom observations were conducted in Payakabung Village, Ogan Ilir Regency, Indralaya. The research method used in this study was purposive sampling method which was carried out with 40 glass bottles containing corn groats, bran, and acacia sawdust as oyster mushroom seed media observed for 5 days which were placed in an incubator (20-25 °C) and storage box (26-30 °C), as well as baglog making using sawdust from various types of wood, namely rubber sawdust (Control Treatment) and acacia sawdust (Treatment 2). The development of oyster mushrooms in the first stage is characterized by the formation of fruiting bodies with a length range of 6.5 cm and reaching a diameter range of 15 cm at 40 days. The stalks and hoods of oyster mushrooms are yellowish white. Average growth of oyster mushroom hyphae on MEA media. Observations showed that oyster mushroom isolates on MEA 1 media (fresh oyster mushroom fruiting bodies) had long hyphal growth, and MEA 2 (farmers› seeds) had fast hyphal growth.